2008
DOI: 10.1177/1524839907309376
|View full text |Cite
|
Sign up to set email alerts
|

Stop the Sores: The Making and Evaluation of a Successful Social Marketing Campaign

Abstract: Although syphilis is a serious disease with long-term consequences if untreated, this increase is particularly worrisome because syphilis is known to facilitate the transmission of HIV (Fleming & Wasserheit, 1999). In Los Angeles, approximately 60% of MSM diagnosed with early syphilis in 2005 were also HIV positive (STDP, Los Angeles County Department of Public Health, 2006). Furthermore, a recent study suggests that acquisition of syphilis and HIV may be occurring concurrently among MSM (Taylor et al., 2005).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Research suggests that public health campaigns that use the principles of social marketing have proven effective in reaching underserved populations at high risk of contracting HIV (Martinez-Donate et al, 2009) and contribute to normalize stigmatized behaviors. However, formative research aimed at understanding appropriate sources is necessary to increase the likelihood that the target population will be exposed to the campaign (Plant et al, 2010). Thus, successful social marketing campaigns to increase awareness begin with the identification of the preferred venues or sources to receive information by target populations (Grier & Bryant, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that public health campaigns that use the principles of social marketing have proven effective in reaching underserved populations at high risk of contracting HIV (Martinez-Donate et al, 2009) and contribute to normalize stigmatized behaviors. However, formative research aimed at understanding appropriate sources is necessary to increase the likelihood that the target population will be exposed to the campaign (Plant et al, 2010). Thus, successful social marketing campaigns to increase awareness begin with the identification of the preferred venues or sources to receive information by target populations (Grier & Bryant, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…One successful example of a Spanish-language mass media social marketing campaign on the CaliforniaÁMexico border documented an increase in HIV testing using radio, print media, a web site, and a toll-free HIV-testing referral hotline (Olshefsky et al, 2007). In addition, a social marketing campaign on syphilis in LAC among MSM reported that the Spanish language portion resulted in an increase in HIV testing (Plant et al, 2008).…”
Section: Aids Care 1207mentioning
confidence: 99%
“…[13], [14] Since then, effective HIV prevention interventions geared toward changing high-risk behavior have been developed, [15] though many of these interventions have been in small-group formats, [16] which tend to be costly (i.e., labor-intensive, require many trained professionals), difficult to implement and sustain, and lack large-scale reproducibility. [17], [18] Thus, online behavioral interventions, particularly low intensity methods, hold much promise for the future of HIV prevention as part of a multifaceted approach to risk reduction, given their relatively low cost to implement and potential to reach a wide audience of at-risk persons efficiently.…”
Section: Introductionmentioning
confidence: 99%